2007
DOI: 10.1002/jrs.1849
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and pulse radiolysis studies of the antioxidant properties of (+)catechin: metal chelation and oxidizing radical scavenging

Abstract: Catechin (5,7,3 ,4 -tetrahydroxyflavan-3-ol, Cat), a compound suggested to give protection to living organisms both by direct scavenging of free radicals and metal chelation, was investigated in the presence of Zn(II) and Cu(II) ions by different techniques.The UV/vis, Raman and IR studies were useful to assess the chelation sites, the relevant interaction of Cat with Cu(II) ions, as well as the weak affinity with Zn(II). Cat acts as a bidentate ligand through the catechol moiety on B-ring, but the metal compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…7 Various metal ions such as Cu , and Ca 2+ exist in the human body. These divalent metal ions are vital for all type of biological functions such as gene expression, apoptosis, enzyme regulation and neurotransmission.…”
Section: 9mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Various metal ions such as Cu , and Ca 2+ exist in the human body. These divalent metal ions are vital for all type of biological functions such as gene expression, apoptosis, enzyme regulation and neurotransmission.…”
Section: 9mentioning
confidence: 99%
“…Some papers reported that oxidation of catechin is mainly carried out in the dissociation of catechol moiety in the initial state. 7,19 It might be therefore concluded that the -OH part of the catechol moiety bound to catechin molecule is first dissociated its anion form and then the ionized chemical species are converted into the oxidized form called quinones receiving help from metal ions.…”
mentioning
confidence: 99%
“…They are contained in green tea, red wine and numerous fruits and vegetables. [9][10][11] Catechin (5,7,3',4'-tetrahydroxyflavan-3-ol), the major constituent of green tea, is one of the flavanol compounds. This substance is a polyphenolic compound in which there are 5 hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…The (+)-catechin ((+)-(2R,3S)-5,7,3',4'-tetrahydroxyflavan-3-ol; Cat Figure 1(a)) is one of the flavonoids extracted from tea plants, gambir (Uncaria gambir), areca (Areca catechu) and so on. The Cat shows reductive action and its catechol group forms complexes with metal ions [5] [6].…”
Section: Introductionmentioning
confidence: 99%